Manajemen Event Kediri Nite Carnival dalam Menguatkan City Branding Kota Kediri - Aji Prasojo; Alif Anggun Yuliasari; Eka Amelia Putri Dinanty (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study examines the management of Kediri Nite Carnival (KNC), an annual event organized by the Kediri City government to commemorate the city's anniversary and showcase local arts, culture, and tourism potential. This research uses qualitative methodology and employs literature analysis, observation, and documentation as case study methods. The Miles and Huberman interactive model is used to analyze the data. The Kediri City Tourism Office has implemented each stage of event management according to Goldblatt's concept: research, design, preparation, coordination, and evaluation. The focus of the research was to determine the objectives and target audience; the design highlighted the local cultural theme “Exotic Flower in Paradise”; planning included budget planning, scheduling, and promotional strategies through social media and collaboration with local media; coordination was carried out through task distribution and cross-team communication; and evaluation assessed the success of the event based on community feedback and its effects on tourism and the local economy. The research results show that KNC plays an important role in improving the public's perception of Kediri City as a creative and cultured city. However, efforts to increase the number of tourist visits in the long term still need to be made. It is hoped that these findings will help the local government develop a sustainable tourism communication plan.